Synthesis, electronic properties, and self-assembly on Au{111} of thiolated phenylethynyl phenothiazines - Barkschat, Christa S.; Stoycheva, Svetlana; Himmelhaus, Michael; Müller, Thomas J. J. (Chemistry of materials, 2010)
Thiolated phenylethynyl phenothiazines can be regarded as redox-active “alligator clips”. They are readily synthesized from ethynyl phenothiazines and show intense blue-green luminescence upon ultraviolet (UV) excitation. Cyclic voltammetry reveals reversible oxidation, also after the chemisorption of in situ liberated thiols on gold electrodes. The chemisorption on Au{111} was studied by ellipsometry, contact angle measurements, X-ray photoelectron spectroscopy, and infrared reflection absorption spectroscopy, and the obtained data support the formation of self-assembled monolayers, depending on the structure of the substrates. These findings classify them as promising candidates for molecular wires switchable by redox manipulation.